Effectiveness of antiarrhythmic drugs for shockable cardiac arrest: A systematic review. (November 2018) - Ali, Muhammad Usman; Fitzpatrick-Lewis, Donna; Kenny, Meghan; Raina, Parminder; Atkins, Dianne L.; Soar, Jasmeet; Nolan, Jerry; Ristagno, Giuseppe; Sherifali, Diana
Abstract: Purpose: The purpose of this systematic review is to provide up-to-date evidence on effectiveness of antiarrhythmic drugs for shockable cardiac arrest to help inform the 2018 International Liaison Committee on Resuscitation Consensus on Science with Treatment Recommendations. Methods: A search was conducted in electronic databases Medline, Embase, and Cochrane Library from inception to August 15, 2017. Results: Of the 9371 citations reviewed, a total of 14 RCTs and 17 observational studies met our inclusion criteria for adult population and only 1 observational study for pediatric population. Based on RCT level evidence for adult population, none of the anti-arrhythmic drugs showed any difference in effect compared with placebo, or with other anti-arrhythmic drugs for the critical outcomes of survival to hospital discharge and discharge with good neurological function. For the outcome of return of spontaneous circulation, the results showed a significant increase for lidocaine compared with placebo (RR = 1.16; 95% CI, 1.03–1.29, p = 0.01). Conclusion: The high level evidence supporting the use of antiarrhythmic drugs during CPR for shockable cardiac arrest is limited and showed no benefit for critical outcomes of survival at hospital discharge, survival with favorable neurological function and long-term survival. Future high quality research is needed to confirm these findings and also to evaluate the role of administering antiarrhythmic drugs in children with shockable cardiac arrest, and in adults immediately after ROSC.